High Performance is Not Always Directly Proportional to Service Quality: A Case of One-stop Service of Sragen - Chairudin, Moehhamad; Setyowati, Kristina; Suharto, Didik G. (UI Scholars Hub, 2018)
One-Stop Service (OSS) of public, investment and business permits (Badan Perizinan Terpadu dan Penanaman Modal/BPTPM) Regency (Kabupaten) of Sragen is considered to have high performance, as evidenced by having received many awards in the field of public services, including four times received the award as the best regency of investment or Investment Award from Badan Koordinasi Penanaman Modal. This research is to test whether high performance can always give satisfactory service quality, and to analyze the cause using Importance Performance Analysis (IPA) method, in terms of six dimensions: tangibles, reliability, responsiveness, assurance, empathy, and accessible, by comparing the expectation of the customers to the actual service performance. Collecting data with randomly questionnaires to 100 customers during period October 24 - November 18, 2016. BPTPM Kabupaten Sragen customers highly expect the best service on reliability dimension, but service performance score on reliability dimension is not good enough, and still less than tangibles, empathy, and responsiveness dimensions score, thereby reducing the level of customer satisfaction. This is what causes the quality of service is not satisfactory, although overall is considered to have a high level of service performance. From this research, it is proven that high service performance, does not always result in satisfactory quality of service, because it is also influenced by the level of customer expectation on each service factors. Thus, service providers should give priority to improve service performance on the aspect most desired by the customers first, to improve the quality of service.